Expansão de um modelo de avaliação de arquitetura de linha de produto de software - Verdecia, Yenisei Delgado (2018)
The primary purpose of a Software Product Line (LPS) is to reduce costs and increase productivity by reusing artifacts. In this approach, the main artifact is the Product Line Architecture (PLA) because it provides a solution for a range of LPS products. Evaluating the PLA design is a fundamental and complex task during the LPS life cycle, since the PLA specifies a set of reusable components in the LPS. The search for solutions to software engineering problems has been addressed in the search field called Search- based Software Engineering (SBSE) through approaches based on Multi-Objective Evolutionary Algorithms (MOEAs), which consider different factors and measures that affect the PLA design problem. In order to evaluate PLA designs, which use different software metrics to evaluate the modularity of characteristics, the PLA extensibility and the basic principles of design, the Multi-Objective Approach for Product Line Architecture Design (MOA4PLA) was proposed. However, other architectural properties can be evaluated. In this context, the objective of the present work was to expand the MOA4PLA evaluation model with metrics that assess other PLA design properties. Therefore, a quality model was defined for the MOA4PLA. After, other metrics have been identified to measure other architectural properties in the proposed quality model. Taking into account the new selected metrics, new objective functions were defined in the MOA4PLA evaluation model and implemented in the tool OPLA-tool. In order to investigate the correlation between the new objective functions, an exploratory study was carried out involving four experiments. Thus, the present work expands the evaluation model of the MOA4PLA, with other metrics to evaluate PLA designs. The main contributions of this work are: the proposal of the quality model for SBPD, the use of metrics for LPS oriented to services applied for the first time in the context of SBPD; and the new objective functions that let evaluate other architectural properties in the evaluation model of MOA4PLA.